Sleep duration and metabolic body size phenotypes among Chinese young workers - Wang, Jiangshui; Xue, Dan; Shi, Bin; Xia, Lu; Chen, Weiyi; Liu, Li; Liu, Junling; Wang, Huaiji; Ye, Fang (Frontiers in Public Health, 2022)
The evidence linking sleep duration and metabolic body size phenotypes is limited, especially in young adulthood. In this study we aimed to examine the association between sleep duration and metabolic body size phenotypes among Chinese young workers and investigate whether discrepancies exist among shift and non-shift workers. A cross-sectional study was performed between 2018 2019 in Wuhan, China and 7,376 young adults aged 20 35 years were included. Self-reported sleep duration was coded into four groups: <7, 7 8, 8 9, and ≥9 hours per day. Participants were classified into four metabolic body size phenotypes according to their body mass index and metabolic health status: metabolically healthy normal weight, metabolically unhealthy normal weight, metabolically healthy overweight/obesity (MHO), and metabolically unhealthy overweight/obesity (MUO). Multinomial logistic regression models were used to explore the associations of sleep duration and metabolic body phenotypes. Compared to those who slept 7 8 hours each night, those with sleep duration <7 hours per day had a higher risk of MHO (OR 1.27, 95% CI: 1.02 1.56) and MUO (OR 1.22, 95% CI: 1.03 1.43), irrespective of multiple confounders. Stratification analyses by shift work showed that the association between short nighttime sleep and increased risk of MUO was only observed in shift workers (OR 1.26, 95% CI 1.03 1.54). Sleep duration is independently associated with metabolic body size phenotypes among Chinese young adults, while shift work could possibly modulate the association. These results may provide evidence for advocating adequate sleep towards favorable metabolic body size phenotypes in young adults.